Socialism, democracy and Europe. Transition and European integration: the Portuguese case - Castaño,David (2018)
The role played by Europe in the Portuguese democratisation process has been analysed primarily by political science, following the line of research developed by «transitology» that drew attention to the importance of the international context. Among the key aspects that stand out in this literature is the idea that the EEC played a particularly relevant role in the democratic consolidation phase. However, Geoffrey Pridham argued that we should not overlook the influence of European integration on democratic transition processes. The present article will follow this line taking a historical approach by analysing the evolution of the Portuguese Socialists in relation to the process of European integration and the EECs role during Portugals democratic transition.